AJARAN BERBUDI DALAM SAMPIRAN PANTUN ADAT MINANGKABAU KARYA N.M. RANGKOTO - Yosi Wulandari; Fitri Merawati (Fakultas Bahasa dan Seni UNP, 2022)
Minangkabau is one of the ethnic groups that have a culture with a strong philosophy of life. The moral teachings summarized in the Minangkabau traditional pantun need to be explored further. The purpose of this study is to describe the ethical teachings in the hook of Minangkabau traditional pantun. This research method is descriptive qualitative. Moral teachings are the object of research that is of concern in this study. The results of this study indicate that the hook in the Minangkabau traditional pantun Part I in five subsections has a meaning that is in line with the content of the pantun. The hook is a symbol that directs the importance of moral teachings that must be guarded and paid attention to by the entire Minangkabau community so that they know how to use words, maintain character, use reason, weigh feelings, and place themselves in attitude.